The Stockholm Estates: A Tale of the Importance of Initial Conditions, Macroeconomic Dependencies, Tenure and Immigration. - Andersson, Roger; Bråmå, Åsa (Springer Open, 2018)
In the chapter, the authors define the concept of housing estates in the Swedish context and provide some information about Stockholm and the historical background to the construction of post-war housing estates. The core research question will then be whether and to what extent initial conditions play a key role for later developments of an estate. Approaching this question, we first provide a statistical overview of developments from 1990 onwards, and then use examples from two estates in Stockholm, one built in the mid-1960s (Bredäng) and one built a few years later (Rinkeby), which now have similar problems of ethnic and socio-economic segregation but have arrived at this situation through very different trajectories. The authors will analyse these trajectories and identify the key moments leading up to present day convergence in terms of the social challenges facing the estates. Until 1990, the socio-economic situation in the 49 estates the authors analysed was not very different from the average situation in the Stockholm region. However, the economic crisis of the early 1990s had profound effects and initiated diverging trajectories where some estates continued to do well while others did not. We explain this diverging development with reference to tenure composition, geographical context and building period, all important for also understanding the geography of refugee settlement. This set of explanations is based both on the more structural analysis of all 49 estates and on the more detailed study of our two cases. The chapter ends with a discussion of 40 years of recurrent interventions and of how contemporary challenges are perceived and addressed.
Keywords: Wohnungswesen; Wohnsiedlung; Segregation; Stadtentwicklung; Migration; Fallbeispiel